Cost effectiveness of typhoid vaccination in India. Issue 30 (5th July 2021) - Chauhan, Akashdeep Singh; Kapoor, Isha; Rana, Saroj Kumar; Kumar, Dilesh; Gupta, Madhu; John, Jacob; Kang, Gagandeep; Prinja, Shankar
Abstract: Introduction: World Health Organization has prequalified the use of typhoid conjugate vaccine (TCV) in children over six months of age in typhoid endemic countries. We assessed the cost-effectiveness of introducing TCV separately for urban and rural areas of India. Methods: A decision analytic model was developed, using a societal perspective, to compare long-term costs and outcomes (3% discount rate) in a new-born cohort of 100, 000 children immunized with or without TCV. Three vaccination scenarios were modelled, assuming the protective efficacy of TCV to last for 5, 10 and 15 years following immunization. Incidence of typhoid infection estimated under 'National Surveillance System for Enteric Fever' (NSSEFI)' was used. The prices of vaccine and cost of service delivery were included for vaccination arm. Both health system cost and out-of-pocket expenditures for treatment of typhoid illness and its complications was included. Results: TCV introduction in urban areas would result in prevention of 17% to 36% typhoid cases and deaths. With exclusion of indirect costs, the incremental cost per QALY gained was ₹ 151, 346 (54, 730–307, 975), ₹ 61, 710 (−5250 to 163, 283) and ₹ 45, 188 (−17, 069 to 141, 093) for scenario 1, 2 and 3 respectively. While, with inclusion of indirect costs, all 3 scenarios were cost saving. Further, in rural areas, TCV is estimated to reduce the typhoid cases and deaths by 19% to 36%, with ICER (incremental cost per QALY gained) ranging from ₹ 2340 (1316–4370) to ₹ 3574 (2057 – 6691) thousand (inclusive of indirect costs) among the 3 vaccination scenarios. Conclusion: From a societal perspective, introduction of TCV is a cost saving strategy in urban India. Further, due to low incidence of typhoid infection, introduction of TCV is not cost-effective in rural settings of India.